1995
DOI: 10.1007/bf02049733
|View full text |Cite
|
Sign up to set email alerts
|

Factors that predict incomplete colonoscopy

Abstract: Women, especially those with a history of abdominal hysterectomy, had a significantly lower cecal intubation rate usually because of an impassable sigmoid colon. Prior inability to complete colonoscopy to the cecum does not necessarily forecast future failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
92
1
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(109 citation statements)
references
References 23 publications
9
92
1
5
Order By: Relevance
“…In the study conducted by Cirocco and Rusin (15), it was reported that previous hysterectomy operations are a factor for failed colonoscopy. While low BMI (<25) was found to be a failure factor in the study conducted by Anderson et al (14), failure was higher in overweight patients in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Cirocco and Rusin (15), it was reported that previous hysterectomy operations are a factor for failed colonoscopy. While low BMI (<25) was found to be a failure factor in the study conducted by Anderson et al (14), failure was higher in overweight patients in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of certain symptoms (altered bowel habits, abdominal pain, diarrhea, constipation, hemorrhage), inflammatory bowel disease, and cancer) were also associated with incomplete examination 16 Completion rates were also lower in women and after hysterectomy. 17 However, even with these limiting factors, the colonoscopic completion rates are still approximately 90% in these subsets of patients. There is no evidence to suggest that incomplete colonoscopy is not associated with a higher complication rate.…”
Section: Discussionmentioning
confidence: 99%
“…57,58 Risk factors for poor bowel preparation quality include older age, overweight, diabetes and other comorbidities. 59,60 In those individuals for whom colonoscopy is difficult and therefore unsuccessful, it is probably inappropriate to recommend repeated colonoscopic surveillance; alternative surveillance strategies need to be explored.…”
Section: Examination Qualitymentioning
confidence: 99%